Active learning for an evidence-based veterinary medicine course during COVID-19 - St-Hilaire, Sophie; Nekouei, Omid; Parkes, Rebecca S. V.; Rosanowski, Sarah M. (Frontiers in Veterinary Science, 2022)
Epidemiology is often a challenging course that is not well appreciated by many students learning veterinary medicine. The curriculum for this topic can sometimes be dry, difficult for students to contextualize, and heavy with statistics and mathematical concepts. We incorporated the concepts of epidemiology that are most important for practicing veterinarians and combined these with evidence-based veterinary medicine principles to create a practical course for second-year undergraduate veterinary students. We share the structure of our course and the different learning components, which also included incorporating graduate student mentors for journal clubs and an assignment that culminated in some students publishing their review findings. Anecdotal responses from students suggest they enjoyed the course and learned skills they felt would be useful in veterinary practice to help them make evidence-based clinical decisions.